2020
DOI: 10.1155/2020/3089063
|View full text |Cite
|
Sign up to set email alerts
|

Access to Functional Handwashing Facilities and Associated Factors among South Sudanese Refugees in Rhino Camp Settlement, Northwestern Uganda

Abstract: Background. Hand hygiene in refugee camp settlements remains an important measure against diarrhoeal infections. Refugee settings are characterised by overcrowding and inadequate access to water and hygiene facilities which favour proliferation of faecal-oral diseases. Handwashing with soap and water is therefore an effective way of preventing such diseases. Despite this knowledge, there is limited information about access to functional handwashing facilities in these settings and associated factors in Uganda.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Research in urban slums in Kenya found a positive association between household size and water consumption [ 28 ], washing hands, and sanitation access [ 29 ]. However, there are limited published studies looking at the relationship between household size and WASH access in refugee camps and settlements [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research in urban slums in Kenya found a positive association between household size and water consumption [ 28 ], washing hands, and sanitation access [ 29 ]. However, there are limited published studies looking at the relationship between household size and WASH access in refugee camps and settlements [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Selection of refugee households was based on the daily use of wood fuel for cooking and residence time in the refugee settlement of at least a year. Data from the interviews were categorised according to household family size, i.e., very small (1-3), small (3)(4)(5), medium (6)(7)(8), large (9)(10)(11)(12), and very large (12)(13)(14)(15), to examine if these influenced the determinants of wood fuel collection and use. In addition, two focus group discussions consisting of 15 members (men, women, youths, elders, village leaders, and cultural leaders) were conducted in each settlement.…”
Section: E Household Survey and Analysismentioning
confidence: 99%
“…e refuge household sizes had a significant contribution on the demand for wood fuel. Depending on the membership of each household, families were categorised as very small (1-3), small (3-5), medium (6)(7)(8), large (9)(10)(11)(12), and very large (12)(13)(14)(15) because these influenced the amount of food cooked and frequency. e household size categories that had a significant contribution to the collection and use of firewood were the large (9-12), medium (6)(7)(8), and very small (1-3) (P < 0.05) (Table 2).…”
Section: Determinants Of Choices Of Wood Fuel Collection and Use By R...mentioning
confidence: 99%
See 2 more Smart Citations